Factors affecting the perceived usefulness and intention to adopt artificial intelligence in manufacturing enterprises in the Southeast region of Vietnam - Lan, Giao Thi Phuong; Khanh, Pham Ngoc (Edelweiss Applied Science and Technology, 2025)
This study aims to explore “Factors affecting the perceived usefulness and intention to adopt artificial intelligence in manufacturing enterprises in the Southeast region of Vietnam.” Based on an integrated framework combining the Technology Acceptance Model (TAM) and the Technology–Organization–Environment (TOE) model, this study analyzes how organizational, technological, and environmental factors influence the adoption of artificial intelligence (AI). By employing a mixed-methods approach—comprising expert interviews and a quantitative survey of 435 manufacturing enterprises—the data were processed using SPSS 29.0 and AMOS 29.0 through several steps: reliability testing, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The results reveal that five factors: government involvement (GI), perceived cost (PC), management support (MS), technical infrastructure (TI), and organizational culture (OC) positively influence perceived usefulness (PU). Meanwhile, competitive pressure (CP) and vendor partnership (VP) have a direct effect on the intention to adopt AI (AAI). Notably, perceived usefulness (PU) plays a significant mediating role and has a strong impact on the intention to adopt AI (AAI). These findings confirm the appropriateness of the TAM model in explaining AI acceptance behavior and provide managerial implications for business leaders and policymakers to promote AI adoption in manufacturing enterprises.